2020
DOI: 10.1111/jbi.13925
|View full text |Cite
|
Sign up to set email alerts
|

Environmental heterogeneity dynamics drive plant diversity on oceanic islands

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 77 publications
(102 reference statements)
6
33
0
Order By: Relevance
“…Species richness for all taxonomic groups in this study was predicted by the GDM (ATT 2 independently for 10 groups and ATT 2 + Isolation + Habitat Diversity for 11 groups; Table S1.4), even though topographic complexity (TC) itself did not follow the hump‐shaped curve as previously predicted. Our findings of ATT 2 as a significant predictor for plants, snails and invertebrates aligns with previous studies (Barajas‐Barbosa et al, 2020; Cameron et al, 2013; Cardoso et al, 2010; Steinbauer et al, 2013; Whittaker et al, 2008), and we also find a similar relationship for higher dispersing organisms such as birds. Therefore, our study largely supports that the hump‐shaped relationship of island age can predict species richness (Whittaker et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Species richness for all taxonomic groups in this study was predicted by the GDM (ATT 2 independently for 10 groups and ATT 2 + Isolation + Habitat Diversity for 11 groups; Table S1.4), even though topographic complexity (TC) itself did not follow the hump‐shaped curve as previously predicted. Our findings of ATT 2 as a significant predictor for plants, snails and invertebrates aligns with previous studies (Barajas‐Barbosa et al, 2020; Cameron et al, 2013; Cardoso et al, 2010; Steinbauer et al, 2013; Whittaker et al, 2008), and we also find a similar relationship for higher dispersing organisms such as birds. Therefore, our study largely supports that the hump‐shaped relationship of island age can predict species richness (Whittaker et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…For plants, we found that the TC indices RE and SE predict species richness in NE_P and improve multiple models in both NE_P and SIE_P. This directly aligns with Barajas‐Barbosa et al’s (2020) findings as four out of five measures of elevation they tested (including RE and SE) increased diversity in both NE and SIE plants (the Galápagos archipelago was included in their data set of 135 volcanic archipelagos).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The generality of the robustness pipeline developed here allows for other studies on the robustness of other models under complex generating processes. Alternative hypotheses for island changes are changing isolation, topographical complexity, or evolution of environmental heterogeneity as new islands undergo succession (Massol et al, 2017;Barajas-Barbosa et al, 2020).…”
Section: Robustness Studies In Phylogeneticsmentioning
confidence: 99%